2022
DOI: 10.1371/journal.ppat.1010868
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and Type 2 Epstein-Barr viruses induce proliferation, and inhibit differentiation, in infected telomerase-immortalized normal oral keratinocytes

Abstract: Differentiated epithelial cells are an important source of infectious EBV virions in human saliva, and latent Epstein-Barr virus (EBV) infection is strongly associated with the epithelial cell tumor, nasopharyngeal carcinoma (NPC). However, it has been difficult to model how EBV contributes to NPC, since EBV has not been shown to enhance proliferation of epithelial cells in monolayer culture in vitro and is not stably maintained in epithelial cells without antibiotic selection. In addition, although there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…As uninfected NOKs spontaneously differentiate in monolayer culture when grown at subconfluent conditions without growth factors, and we previously showed that WT-EBV infection inhibits this differentiation ( 14 ), we determined if LMP1 expression is also required for this EBV effect. Immunoblot analyses were performed to compare expression levels of cell cycle markers and markers of epithelial cell differentiation when uninfected, WT-EBV infected, or ∆LMP1-infected NOKs were grown in growth-factor restricted conditions for 24 h. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As uninfected NOKs spontaneously differentiate in monolayer culture when grown at subconfluent conditions without growth factors, and we previously showed that WT-EBV infection inhibits this differentiation ( 14 ), we determined if LMP1 expression is also required for this EBV effect. Immunoblot analyses were performed to compare expression levels of cell cycle markers and markers of epithelial cell differentiation when uninfected, WT-EBV infected, or ∆LMP1-infected NOKs were grown in growth-factor restricted conditions for 24 h. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NOKs provide an excellent model system to study EBV in epithelial cells since they can be stably infected with EBV (in the presence of antibiotic selection) and retain the ability to differentiate ( 4 , 11 13 ). Although we recently showed that EBV infection of NOKs inhibits spontaneous differentiation and promotes proliferation when cells are grown in monolayer culture in the absence of supplemental growth factors ( 14 ), suspended in methylcellulose ( 12 ), or “rafted” ( 12 ), the mechanism(s) for these effects and the specific viral protein(s) and/or viral RNAs required have not been previously identified. We show here that mutation of the EBV LMP1 gene greatly reduces the ability of EBV infection to enhance cellular proliferation and inhibit spontaneous differentiation in NOKs when growth factors are limiting.…”
mentioning
confidence: 99%
“…Likewise, HPV16 oncoprotein E6 induces cell proliferation by dephosphorylating a serine residue of YAP1 (S379) and preventing its degradation by the proteasome complex (He et al, 2015). More recently, it has been discovered that Epstein-Barr virus subverts the YAP/TAZ pathway in lytic reactivation in epithelial cells (Singh et al, 2023a; Van Sciver et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A GFP/G418R cassette was inserted into the non-essential BXLF1 gene of the AG876 type 2 EBV strain genome in the AG876 BL cell line by homologous recombination using G418 selection, and then stably infected HeLa cell clones containing this virus were derived as previously described [ 84 ]. The CRISPR/CAS9 technique was used in the AG876 virus-infected HeLa cells to create a mutation in the EBNA2 gene that puts the reading sequence out-of-frame at EBNA2 residue 25.…”
Section: Methodsmentioning
confidence: 99%